Pengaruh Supervisi dan Coaching Kepala Ruangan terhadap Kinerja Perawat - Monika Isti Indriasari; Emiliana Tarigan (Syntax Corporation Indonesia, 2024)
Objectives: To explore the effect of supervision and coaching by the head of the ward on nurses' performance. Methods: This study used a literature review method that involved surveying various sources such as journals, books, documentation, internet, and literature relevant to the object of research. PICOT framework was used to search for international online journals with the keywords “Supervision, Coaching, Nurse Performance. Results: The findings reveal that supervision and coaching provided by head nurses or nurse management significantly impact their performance. Research outcomes from various sources indicate that supervision, whether in the form of peer group supervision, clinical supervision, PRIMA, or ESA-C, demonstrate improvements in knowledge, attitudes, skills, and the evaluation of nursing care. Meanwhile, coaching, especially within training programs, has proven to assist in identifying individual and team needs, enhancing competence, and improving nurse performance by providing guidance, reflection, and necessary emotional support. Conclusion: Head nurse supervision and coaching play pivotal roles in enhancing nurse performance across various hospital contexts. When effectively implemented by leaders, these factors can elevate the quality of healthcare services provided by nurses in hospital settings.